The PERAN KOMUNIKASI DAKWAH DALAM MENINGKATKAN KUALITAS AKADEMIK DI PESANTREN MUHAMMADIYAH BOARDING SCHOOL ENREKANG - Syahruddin, Muhammad; Istiwanti, Ayu; Tike, Arifuddin; B Wulur, Meisil (Jurnal Kajian Manajemen Dakwah, 2023)
This research aims to find out how academic activities are, the role of da'wah communication in improving academic quality, and supporting and inhibiting factors for da'wah communication at Islamic Boarding School Muhammadiyah Boarding School Enrekang. This research is descriptive qualitative. Collecting data using the method of observation, interviews and documentation. The results of the research show that the role of da'wah communication in improving academic quality at the Islamic Boarding School Muhammadiyah Boarding School Enrekang is quite successful. The da'wah communication of the leaders of the Enrekang Muhammadiyah Boarding School to the students has made the quality of the students increasingly developed in terms of memorization, behavior, especially their ability to give lectures in the community. For this reason, the objective of establishing the Muhammadiyah Boarding School Enrekang Islamic Boarding School is gradually starting to materialize. Apart from that, the da'wah communication of the leaders of the Muhammadiyah Boarding School Enrekang Islamic Boarding School to the community was accepted, so that the existence of the Muhammadiyah Boarding School Enrekang Islamic Boarding School began to be known. As a new Islamic boarding school, known and recognized by the community, this is a form of extraordinary development.